2020
DOI: 10.1002/mus.26905
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mechanical ventilation in children with Guillain‐Barré syndrome

Abstract: BackgroundWe assessed clinical predictors of mechanical ventilation in children with Guillain‐Barré syndrome (GBS) to help identify patients who require mechanical ventilation.MethodsWe retrospectively collected the clinical, laboratory, and electrophysiological data of 103 children with GBS. Patients were categorized into two groups based on the requirement for mechanical ventilation. Variables that were significantly different between the two groups in univariate analysis were analyzed by multivariate logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…Regarding EDx results, we found no difference in GBS subtypes in the group with respiratory failure, which is consistent with some studies ( Green, Baker & Subramaniam, 2018 ; Parveen et al, 2020 ) but contradicts others where a higher proportion of demyelinating ( Durand et al, 2006 ; Yamagishi et al, 2017 ) or axonal GBS subtypes was found ( Shangab & Al Kaylani, 2021 ; Walgaard et al, 2010 ; Islam et al, 2019 ; Luo et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding EDx results, we found no difference in GBS subtypes in the group with respiratory failure, which is consistent with some studies ( Green, Baker & Subramaniam, 2018 ; Parveen et al, 2020 ) but contradicts others where a higher proportion of demyelinating ( Durand et al, 2006 ; Yamagishi et al, 2017 ) or axonal GBS subtypes was found ( Shangab & Al Kaylani, 2021 ; Walgaard et al, 2010 ; Islam et al, 2019 ; Luo et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, the multivariate analysis showed that the only significant predictors were bulbar palsy (AOR 10.4) and weakness of hip flexors of MRC ≤ 3 (AOR 31.4). By comparison, bulbar weakness was a significant predictor of respiratory failure in several studies ( Malaga et al, 2021 ; Kanikannan et al, 2014 ; Toamad et al, 2015 ; Wu et al, 2015 ; Green, Baker & Subramaniam, 2018 ; Islam et al, 2019 ; Umer et al, 2019 ; Luo et al, 2020 ; Ning et al, 2020 ). Although the short time from symptom onset to admission (≤7 days) was a significant predictor in several studies ( Rantala et al, 1995 ; Toamad et al, 2015 ; Wu et al, 2015 ; Green, Baker & Subramaniam, 2018 ; Umer et al, 2019 ; Luo et al, 2020 ), it did not reach statistical significance in our univariate and multivariate analyses.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similar to adult cohorts, requirement for mechanical ventilation in pediatric patients has been associated with facial weakness, cranial nerve involvement, more severe muscle weakness, time from symptom onset to admission, axonal variant GBS, and dysautonomia. 32,56,57 Reported prognosis was not as favorable in a study of a pediatric cohort from Abbreviations: EGOS, Erasmus Guillain-Barre Syndrome Outcome Score; GBS, Guillain-Barre syndrome. Predictions corresponding to these prognostic scores range from 1 to 52% for the inability to walk independently at 6 months.…”
Section: Prognosis In Pediatric Populationsmentioning
confidence: 99%
“…In this disease, autonomic dysfunction is common but rarely lasts more than one or two weeks [3]. There is no definitive cure for Guillain-Barre, but there are ways to improve symptoms, most of which include IVIG and plasmapheresis [4,5]. Guillain-Barre syndrome is an autoimmune disorder characterized by a group of different clinical and pathological findings.…”
Section: Introductionmentioning
confidence: 99%